ANALISIS MODEL FUNDRAISING DAN DISTRIBUSI DANA ZIS DI UPZ DESA WONOKETINGAL KARANGANYAR DEMAK - Murtadho Ridwan (Jurnal Penelitian, 2016)
The success of the collection and distribution of ZIS funds determined by the management of fundraising and distribution adopted by the institution of zakat. There are several models of fundraising and distribution of ZIS funds that can be applied in managing the ZIS funds. UPZ is one part of the organization's most end zakat according to our regulations. UPZ has the authority to collect zakat and charity donation fund. This article aims to analyze the model of fundraising and distribution of ZIS funds in UPZ Wonoketingal village, Karanganyar, Demak. The approach used is a qualitative approach to observation, interviews, and documentation as methods of data collection. When the analysis of the data used is the analysis model of Miles and Huberman. The results showed that fundraising in the UPZ Wonoketinggal village combining two models, namely direct and indirect fundraising. Indirect fundraising is used to promote the program through announcements in lectures, town hall or at the time of Jumu'ah prayer. And direct fundraising committee UPZ done by visiting the houses of citizens directly. While the distribution model of ZIS funds applied consumerist traditional models and creative productive models. Consumptive traditional models used to distribute zakat fitrah, zakat mal for the poor, and funds charitable donation. While creative productive models used for the distribution of zakat mal for gharim.